Impact and habitability scenarios for early Mars revisited based on a 4.45-Ga shocked zircon in regolith breccia - Cox, Morgan; Cavosie, Aaron; Orr, Kenneth; Daly, L.; Martin, L.; Lagain, Anthony; Benedix, Gretchen; Bland, Phil (AMER ASSOC ADVANCEMENT SCIENCE, 2022)
After formation of a primordial crust, early impacts influenced when habitable conditions may have occurred on Mars. Martian meteorite Northwest Africa (NWA) 7034 is a regolith breccia that contains remnants of the earliest Martian crust. The paucity of shock deformation in NWA 7034 was previously cited as recording a decline in giant impacts by 4.48 billion years and evidence for habitable Mars by 4.2 billion years ago. We present new evidence of high-pressure shock effects in a 4.45-billion year-old zircon from the matrix of NWA 7034. The zircon contains (112) shock twins formed in the central uplift of a complex impact structure after 4.45 billion years and records impact pressures of 20 to 30 gigapascals. The zircon represents the highest shock level reported in NWA 7034 and paired rocks and provides direct physical evidence of large impacts, some potentially life-affecting, that persisted on Mars after 4.48 billion years.